The Correlation Between Reading and the Ability of Students in Expository Writing - Siregar, Adelina; Junaidi (Education & Learning, 2022)
Reading is one of skills in English which can get and take the infromation from printed text. Based on preliminary reasearch at SMP Negeri 1 PantaiLabu it was found that the students’ reading score was still low. The objective of this research was to know there was apositive correlation between the students’ reading and the ability at the first semesterof the seven grade of SMP Negeri 1 PantaiLabuin the academic year of 2019/2020. In this research, methodology of the research is a correlation research. In the taking the sample of the research was gained through simple random sampling. The population of the research was taken from students of the seven grade of SMP Neger 1 PantaiLabu The researcher took 40 students from 100 population. In collecting the data, the researcher used question and answer method to measure students’ reading and the ability. Thetry out of question and answer was done to find out the validity and reliability. Then a try out reading ability test was also done to find out the validity and reliability. After the data of students’ reading ability were collected, the data were statistically computed, to find out the correlation between students’ reading and the ability. From the data analysis, the result of applying the distribution shows that coefficient correlation is possitive correlation between students’ reading and the ability of students in expository writing at the first semester of the seven grade of SMP Negeri 1 PantaiLabuin academic year of 2019/2020. From this research, it is suggesed that students have good a reading ability.